Effects of iTBS-rTMS on the Behavioral Phenotype of a Rat Model of Maternal Immune Activation - Rittweger, Nadine; Ishorst, Tanja; Barmashenko, Gleb; Aliane, Verena; Winter, Christine; Funke, Klaus (Frontiers in Behavioral Neuroscience, 2021)
Repetitive transcranial magnetic stimulation (rTMS) is considered a promising therapeutic tool for treating neuropsychiatric diseases. Previously, we found intermittent theta-burst stimulation (iTBS) rTMS to be most effective in modulating cortical excitation-inhibition balance in rats, accompanied by improved cortical sensory processing and sensory learning performance. Using an animal schizophrenia model based on maternal immune activation (MIA) we tested if iTBS applied to either adult or juvenile rats can affect the behavioral phenotype in a therapeutic or preventive manner, respectively. In a sham-controlled fashion, iTBS effects in MIA rats were compared with rats receiving vehicle NaCl injection instead of the synthetic viral strand. Prior to iTBS, adult MIA rats showed deficits in sensory gating, as tested with prepulse inhibition (PPI) of the acoustic startle reflex, and deficits in novel object recognition (NOR). No differences between MIA and control rats were evident with regard to signs of anxiety, anhedonia and depression but MIA rats were somewhat superior to controls during the training phase of Morris water maze test. MIA but not control rats significantly improved in PPI following iTBS at adulthood but without significant differences between verum and sham application. If applied during adolescence, verum but not sham-iTBS improved NOR at adulthood but no difference in PPI was evident in rats treated either with sham or verum-iTBS. MIA and control rat responses to sham-iTBS applied at adulthood differed remarkably, indicating a different physiological reaction to the experimental experiences. Although verum-iTBS was not superior to sham-iTBS, MIA rats seem to benefit from the treatment procedure in general, since differences to control rats declined or disappeared. Even if classical placebo effects can be excluded, motor or cognitive challenges or the entire handling procedure during the experiments appear to alleviate the behavioral impairments of MIA rats.